Persist to desist: How to maintain desistance from crime in the face of severe setbacks - Gålnander, Robin (Criminology & criminal justice, 2024)
Focusing on how to deal with relapses when trying to desist from crime, this article utilises findings from a qualitative and prospective interview study to illustrate what it means to desist. Ten women’s desistance journeys have been studied longitudinally since 2015. Over these years, the women have encountered setbacks and relapses, yet somehow persevered on their path towards a different ‘normal’ life, free from crime, condemnation and marginalisation. Their struggle highlights the need for persistence to sustain desistance from crime. Persistence and desistance are generally conceptualised as each other’s counterparts within life-course criminology, yet putting persistence at the heart of desistance journeys can deepen our understanding of the process involved.